2004
DOI: 10.1111/j.0742-2822.2004.02163.x
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Dimensional Transesophageal Echocardiographic Delineation of Ventricular Septal Aneurysm Producing Right Ventricular Outflow Obstruction in an Adult

Abstract: We report three-dimensional echocardiographic delineation of a congenital aneurysm of the membranous interventricular septum causing right ventricular outflow tract obstruction in an adult patient. To our knowledge, these findings have not been described before.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 5 publications
(8 reference statements)
0
13
0
Order By: Relevance
“…[9][10][11][12] Because the current case had no demonstrable systolic narrowing of the RV outflow tract on echocardiography or angiography, but instead had rapid emptying of the inflow portion of the ventricle caused by the septal excursion powered by LV systole, the dynamic pressure gradient, comparable to the Doppler-derived gradient, was thought to have been caused by cavity obliteration. 13 Although oximetry suggested that there were 2 separate increments in oxygen saturation, with a higher value in the PA than in the RV, there was no echocardiographic, angiographic, or intraoperative evidence of a patent ductus arteriosus.…”
Section: Discussionmentioning
confidence: 81%
“…[9][10][11][12] Because the current case had no demonstrable systolic narrowing of the RV outflow tract on echocardiography or angiography, but instead had rapid emptying of the inflow portion of the ventricle caused by the septal excursion powered by LV systole, the dynamic pressure gradient, comparable to the Doppler-derived gradient, was thought to have been caused by cavity obliteration. 13 Although oximetry suggested that there were 2 separate increments in oxygen saturation, with a higher value in the PA than in the RV, there was no echocardiographic, angiographic, or intraoperative evidence of a patent ductus arteriosus.…”
Section: Discussionmentioning
confidence: 81%
“…echocardiography, cardiac CT, cardiac MRI, or angiography 1. Possible complications include arrhythmias, thromboembolism, right ventricular outflow tract (RVOT) obstruction, rupture, significant tricuspid regurgitation, and endocarditis [2][3][4]. Our patient did not have any of these conditions.…”
mentioning
confidence: 80%
“…Indeed, the most common presentation of ventricular septal aneurysm is in association with VSDs6, 19. Aneurysms of the membranous portion of the ventricular septum and its related heart defects have been associated with serious complications such as right outflow tract obstruction25–27, aortic valve prolapse8, spontaneous rupture3, 10, tricuspid insufficiency, bacterial endocarditis8 and cerebral infarction secondary to embolism28. In some of these cases the therapeutic approach is resection of the sacular dilatation of the septum and closure of the defect8.…”
Section: Discussionmentioning
confidence: 99%
“…This observation is consistent with previous reports which demonstrated that in infants and adults, aneurysms of the membranous septum bulge into the right ventricle due to higher pressure in the left ventricle17, 32, 42. Indeed, functional obstruction of the outflow tracts is more frequently seen in the right side, postnatally25–27.…”
Section: Discussionmentioning
confidence: 99%